2022
DOI: 10.56825/bufbu.2022.4143718
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric study of slaughtered Murrah buffalo bull testis and its correlation with seminal attributes of epididymal semen

Abstract: Present study was conducted to study the morphometric characteristics of slaughtered Murrah buffalo bull testis and its correlation with seminal attributes of epididymal semen. Total 56 pair of slaughtered Murrah buffalo bull testicles were procured from Allana, slaughterhouse, Arrora, and Mass agro food Pvt. Ltd. Unnao Uttar Pradesh, India; maintained at Deep Frozen Semen Laboratory, College of Veterinary science, and animal Husbadry, Ayodhya, Uttar Pradesh, India. Various morphometric parameters of testes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…Moderate but significant ( p < .05) correlation of sperm motility with SC, SV and PTW reported in Nellore bulls of Brazil (Viu et al., 2015). In Murrah buffalo bulls (Kumar & Srivastava, 2017), testicular volume showed very high significant positive correlation ( r = .88–.90) with sperm concentration, motility, HOS reactive spermatozoa and negative correlation with total sperm abnormality ( r = −.81). The significant correlations of testicular traits with semen parameters indicated that at least part of the genes involved in the expression of these traits are same.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate but significant ( p < .05) correlation of sperm motility with SC, SV and PTW reported in Nellore bulls of Brazil (Viu et al., 2015). In Murrah buffalo bulls (Kumar & Srivastava, 2017), testicular volume showed very high significant positive correlation ( r = .88–.90) with sperm concentration, motility, HOS reactive spermatozoa and negative correlation with total sperm abnormality ( r = −.81). The significant correlations of testicular traits with semen parameters indicated that at least part of the genes involved in the expression of these traits are same.…”
Section: Discussionmentioning
confidence: 99%